Thermal insulation type PVB composite film and preparation method and application thereof
Patent Information
- Application Number
- CN202611090166.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种隔热型PVB复合膜及其制备方法与应用,解决了现有隔热薄膜中无机金属氧化物介质造成的通讯信号屏蔽衰减,以及无机纳米颗粒易在有机树脂基体中团聚而降低薄膜光学透过率的问题
1、本发明的隔热型PVB复合膜通过采用有机共轭分子替代传统的无机金属氧化物作为隔热介质,改变了材料的电磁学属性。由于有机共轭分子内部缺乏自由电子载流子,其非金属纯有机体系对射频电磁波呈透射状态。这种材料体系使得复合膜在吸收近红外波段辐射实现隔热的同时,消除了材料对2.4GHz或5GHz等高频通讯信号的反射与衰减损耗,解决了智能建筑和车载玻璃环境中通讯信号被屏蔽的技术瓶颈。
Smart Images

Figure CN122898087A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer thin film materials technology, specifically to a heat-insulating PVB composite film, its preparation method, and its application. Background Technology
[0002] Polyvinyl butyral (PVB) film is widely used in the manufacture of laminated glass for automotive windshields and building curtain walls due to its excellent optical transparency, adhesion, and impact resistance. With increasing energy-saving requirements, endowing PVB laminated glass with thermal insulation properties has become a key focus of industry research and development. Currently, existing technologies for modifying PVB films for thermal insulation mainly employ inorganic nanofiller doping. Commonly used inorganic nanofillers include ITO, ATO, CWO, and nano-titanium dioxide. Their thermal insulation principle relies on the reflection and scattering of near-infrared light by nanoparticles to achieve heat insulation.
[0003] However, this material system based on inorganic metal oxides has significant limitations in practical applications. Inorganic metal oxide fillers can block signals from mobile phones, 5G, and automotive radar, making them unsuitable for smart vehicle and smart building scenarios. When such heat-insulating films are applied to high-end automotive or architectural glass, they can cause attenuation of related wireless signals, failing to meet the signal compatibility requirements of modern devices.
[0004] Meanwhile, the surface energy difference between inorganic metal powder and organic PVB resin matrix is significant, resulting in poor interfacial compatibility. In conventional processing, inorganic nanoparticles are prone to secondary agglomeration in polymer melts. This agglomeration not only weakens the overall thermal insulation performance of the material but also exacerbates light scattering within the film, leading to increased haze and decreased visible light transmittance in laminated glass. Consequently, it becomes difficult for the product to simultaneously achieve both high thermal insulation and high light transmittance. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a heat-insulating PVB composite film, its preparation method, and its application. This solves the problems of communication signal shielding and attenuation caused by inorganic metal oxide media in existing heat-insulating films, and the problem of inorganic nanoparticles easily agglomerating in organic resin matrices, thus reducing the optical transmittance of the film.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a heat-insulating PVB composite film, which adopts the following technical solution: A heat-insulating PVB composite film, wherein the composite film contains no inorganic nanoparticles or inorganic oxide fillers, and the composite film is made from raw materials comprising the following parts by weight: PVB resin: 60-80 parts; Organic conjugated small molecule heat insulation agent: 2-5 parts; Bio-based plasticizer: 8-15 parts; Anti-migration agent: 1-3 parts; Antioxidant: 0.2-0.8 parts; UV stabilizer: 0.5-1.5 parts; Dispersant: 0.3-0.8 parts.
[0007] By adopting the above technical solution, the formulation system of this invention explicitly excludes inorganic nanoparticles and inorganic oxide fillers. This pure organic system design eliminates light scattering sources caused by the agglomeration of inorganic particles inside the composite membrane, and also cuts off the pathway for free electrons that would cause radio frequency signal shielding.
[0008] In terms of thermal insulation mechanism, the unique conjugated single and double bond framework structure of the organic conjugated small molecule thermal insulation agent is utilized. This structure, through its delocalized electron system, absorbs near-infrared light radiation energy, thereby achieving thermal insulation. Since the entire film contains no metal components, radio frequency electromagnetic waves are transmitted through it, maintaining the lossless transmission of communication signals.
[0009] Furthermore, the small difference in interfacial tension between the bio-based plasticizer, the PVB resin matrix, and the organic conjugated small molecule heat-insulating agent in the formulation, combined with the synergistic effect of the anti-migration agent, promotes the homogeneous distribution of organic components within the polymer cross-linking network. This avoids localized agglomeration and fogging from a material compatibility perspective, maintaining not only the optical uniformity of the composite film but also ensuring the basic structural strength of the material.
[0010] Preferably, the composite membrane is made from raw materials comprising the following parts by weight: PVB resin: 65-75 parts; Organic conjugated small molecule heat insulation agent: 2.5-4 parts; Bio-based plasticizer: 10-14 parts; Anti-migration agent: 1.5-2.5 parts; Antioxidant: 0.3-0.7 parts; UV stabilizer: 0.8-1.4 parts; Dispersant: 0.3-0.7 parts.
[0011] By adopting the above technical solution and controlling the mass ratio of the continuous polymer phase to each functional dispersed phase, the free volume inside the resin can be matched with the amount of additive filling.
[0012] This ratio limit not only ensures that the elongation at break of the material does not deteriorate, but also provides the composite film with a stable near-infrared radiation absorption efficiency.
[0013] Preferably, the organic conjugated small molecule heat-insulating agent is a modified cyanine dye, a BODIPY-type modified dye, a DA structure derivative, a polyimide oligomer, or a benzobisthiophene-type conjugated molecule; The bio-based plasticizer is a furfuryl alcohol-based plasticizer or a rosin-based plasticizer; The anti-migration agent is a polyurethane oligomer anti-migration agent or a polysiloxane-grafted PVB anti-migration agent. The UV-resistant agent is a HALS-grafted PVB UV-resistant agent; The dispersant is an organic amine dispersant; The antioxidant is antioxidant 1010.
[0014] By employing the above technical solutions, the organic conjugated molecules are modified with alkoxy groups or their chain lengths are limited. The main purpose is to increase their steric hindrance and match the hydrophobic PVB acetal network, thereby preventing phase separation during processing or later use.
[0015] The selected furfuryl alcohol-based plasticizer and rosin-based plasticizer are bio-based materials. Their molecular structures contain active groups that interact with the matrix, which can effectively regulate the flexibility of the polymer chain segments.
[0016] In terms of suppressing the precipitation of small molecules, polyurethane oligomer anti-migration agents, polysiloxane-grafted PVB anti-migration agents, and HALS-grafted PVB UV-resistant agents are used. The core mechanism is to utilize the entanglement effect of the longer molecular chain segments of oligomers or grafts, combined with the chemical anchoring mechanism of groups, to confine the heat-insulating molecules and UV-resistant groups inside the resin network, thereby blocking the heat-induced precipitation path of small molecules.
[0017] The organic amine dispersant used in combination reduces the interfacial free energy between components by relying on surface activity, thus promoting homogeneous stability; at the same time, the free radical scavenging effect of antioxidant 1010 can further inhibit the thermo-oxidative degradation of polymers.
[0018] Preferably, the PVB resin has an acetal degree of 62%-68%, a hydroxyl content of 20%-22%, a viscosity of 38-55 mPa·s, and a molecular weight of 30,000-40,000.
[0019] By adopting the above technical solution, controlling the acetal degree and molecular weight of PVB resin within a specific range is to enable the resin phase to provide intermolecular pores of appropriate size, thereby better accommodating the intercalation of additives.
[0020] In particular, by controlling the retention of 20%-22% polar hydroxyl groups on the molecular chain segments, these hydroxyl groups can form an intermolecular hydrogen bond network with the polar groups in organic conjugated small molecule heat insulation agents and bio-based plasticizers. The establishment of the hydrogen bond network not only improves the binding strength between the various organic components, but also enhances the overall cohesive energy of the composite membrane.
[0021] Secondly, the present invention provides a method for preparing a heat-insulating PVB composite film, which adopts the following technical solution: A method for preparing a heat-insulating PVB composite film includes the following steps: PVB resin is dried and pulverized to obtain PVB resin powder; Organic conjugated small molecule heat insulation agent, dispersant and anti-migration agent are mixed, PVB-compatible solvent is added, and ultrasonic dispersion is formed to form a uniform dispersion. The dried PVB resin powder was added to the reaction vessel, and butyraldehyde and solid acid catalyst were added to carry out the acetal reaction. The uniformly dispersed liquid was then slowly added dropwise to continue the reaction. At the same time, a bio-based plasticizer, antioxidant, and UV stabilizer were added and stirred until homogeneous. A neutralizer was then added to neutralize the catalyst, resulting in a composite resin solution. The composite resin solution is cast into a film using a casting machine; The formed film is heat-set, cooled, trimmed, and wound up to obtain the finished organic conjugated small molecule heat-insulating PVB composite film without inorganic nanofillers.
[0022] By adopting the above technical solution, this preparation method uses an in-situ composite process to replace the conventional high-temperature melt blending method used in the industry, avoiding the problem of uneven filler dispersion caused by insufficient mechanical shear force in conventional processes. Its core process principle lies in: In the pretreatment, the organic conjugated small molecule heat insulation agent and anti-migration agent are stripped and depolymerized in PVB-compatible solvent by ultrasonic cavitation, and a primary uniform dispersion system is formed by adjusting the surface energy of the dispersant.
[0023] In the initial stage of the acetal reaction, under heating conditions in the reactor, the free hydroxyl groups on the surface of the resin powder come into contact with butyraldehyde molecules and undergo nucleophilic addition and dehydration condensation reactions in the acidic environment provided by the solid acid catalyst. Adjacent hydroxyl groups combine with butyraldehyde to form a polymer backbone containing a six-membered acetal ring. At this time, the polymer network is in an extended state of spatial dynamic rearrangement.
[0024] By seizing this window of opportunity for network expansion, a uniform dispersion is slowly added dropwise to the system for in-situ composite synthesis. The polymer macromolecules, in their active growth phase and with active chain segment movement, open up their internal free volumes. Organic conjugated small molecules then intercalate and embed themselves in the gaps between newly grown acetal segments, establishing a homogeneous molecular-level dispersion structure through in-situ polymerization.
[0025] The bio-based plasticizer and anti-aging agent added simultaneously are connected to the reaction network through hydrogen bonds and van der Waals forces. Then, a neutralizing agent is added to consume the free acid components inside the system and terminate the acetal reaction, thereby stabilizing the above homogeneous structure.
[0026] Finally, in the casting stage, the composite resin solution is extruded through a casting process. Under heat, volatile solvents escape, and the resin polymer matrix and the homogeneously distributed organic materials inside undergo chain segment shrinkage orientation and physical cross-linking as the solvent is removed. After the heat setting process eliminates the residual internal stress of the polymer phase, a composite film with uniform thickness and continuous internal structure is formed upon cooling.
[0027] Preferably, in the step of drying and pulverizing PVB resin, the PVB resin is placed in an oven at 60-80℃ and dried for 2-4 hours, with the moisture content controlled to be ≤0.3%, and then pulverized into powder of 50-100 mesh. In the step of forming a uniform dispersion, the ultrasonic dispersion power is 350-450W and the ultrasonic dispersion time is 15-20min.
[0028] By adopting the above technical solution, the moisture content of PVB resin is limited to ≤0.3% in order to prevent the chemical equilibrium from shifting backward due to excess moisture in the subsequent acetal reaction system, which could lead to polymer hydrolysis side reactions.
[0029] For the preparation of dispersions, setting specific ultrasonic dispersion parameters can provide sufficient mechanical energy to break up agglomerated structures while avoiding the breakage of conjugated double bonds in organic molecules due to ultrasonic energy overload.
[0030] Preferably, in the acetal reaction step, the reaction temperature is controlled at 70-80℃, the reaction time is 1.5-2.5h, and the solid acid catalyst is p-toluenesulfonic acid, the amount of p-toluenesulfonic acid used is 0.8%-1.2% of the mass of PVB resin; The reaction time after adding the uniformly dispersed liquid is 1-1.5 hours. At the same time, bio-based plasticizers, antioxidants, and UV stabilizers are added and stirred at 300-500 r / min until homogeneous. The viscosity of the composite resin solution obtained after the reaction was controlled at 700-1000 mPa·s at 25℃.
[0031] By adopting the above technical solution, the reaction temperature and catalyst dosage can be set to maintain the acetal reaction rate within a constant range, thereby matching the rate of polymer molecular chain rearrangement with the droplet addition rate of the dispersion.
[0032] Controlling the stirring speed and extending the later reaction time can enhance the mass transfer and diffusion of the in-situ composite system. Furthermore, locking in the final viscosity of the composite resin solution aims to ensure that the polymer solution system is in a rheological state suitable for the casting coating equipment, thereby providing adequate leveling performance for the film-forming process.
[0033] Preferably, in the film casting step, the casting temperature is 100-120℃, the casting speed is 0.5-1m / min, and the film thickness is controlled at 0.38-1.14mm; In the heat setting step, the heat setting temperature is 100-110℃, the heat setting time is 3-5 minutes, and then cooling is performed at 20-30℃.
[0034] By adopting the above technical solution, the solvent evaporation gradient between the solution surface and the interior can be adjusted by controlling the temperature and speed parameters during the casting stage.
[0035] This avoids the formation of a skin on the film surface and the generation of pore defects inside the substrate due to excessively rapid solvent escape.
[0036] When combined with a heat setting process at a specified temperature and time, it can effectively relax polymer chain segments that are forced to orient due to casting traction force, and eliminate residual internal stress caused by dimensional deformation during film forming.
[0037] Thirdly, this invention provides an application of a heat-insulating PVB composite film, employing the following technical solution: An application of a heat-insulating PVB composite film, wherein the composite film is used in the fields of high-end automotive glass, high-end architectural glass, photovoltaic glass, high-end display glass, and medical glass; The composite film, as a sandwich layer with high light transmittance, low haze, high-efficiency heat insulation and no signal shielding performance, is used in automotive HUD glass sandwich layers, new energy vehicle skylight glass, high-end office building curtain wall glass, photovoltaic module sandwich glass, OLED display panel sandwich glass, and operating room glass partitions.
[0038] By adopting the above technical solution, the composite membrane layer is constructed entirely from a pure organic medium system.
[0039] This non-metallic molecular framework possesses excellent wave transmission properties, and after being laminated into a laminated glass assembly, it does not hinder the penetration and interaction of wireless radio frequency electromagnetic waves in various operating frequency bands.
[0040] Therefore, while ensuring that the building facade or vehicle interior blocks the input of external infrared thermal radiation energy, the film avoids the signal reflection loss problem caused by the presence of metallic dielectric materials.
[0041] This satisfies the practical engineering requirements of modern communication technology equipment for signal transmission fidelity and the optical transparency of the glass substrate itself from the application perspective.
[0042] This invention provides a heat-insulating PVB composite film, its preparation method, and its application. It has the following beneficial effects: 1. The heat-insulating PVB composite film of this invention uses organic conjugated molecules instead of traditional inorganic metal oxides as the heat-insulating medium, thereby altering the electromagnetic properties of the material. Because organic conjugated molecules lack free electron carriers, their non-metallic, purely organic system is transmissive to radio frequency electromagnetic waves. This material system allows the composite film to absorb near-infrared radiation for heat insulation while eliminating the reflection and attenuation loss of high-frequency communication signals such as 2.4GHz or 5GHz, thus solving the technical bottleneck of communication signal shielding in smart buildings and automotive glass environments.
[0043] 2. This invention introduces an in-situ composite mechanism in the preparation process to improve the dispersibility of materials. During the acetal reaction in the reactor, when the polymer spatial network is in a stage of dynamic rearrangement, an organic conjugated molecule dispersion is directly added dropwise. Organic functional molecules take this opportunity to intercalate between the newly grown acetal segments, and combined with the low interfacial tension between the matrix, achieve a homogeneous molecular-level distribution within the polymer. This process avoids the agglomeration problem caused by insufficient shear force in traditional melt blending, ensuring the uniformity of the internal structure of the composite film and the optical transmittance of the final laminated glass.
[0044] 3. The formulation system of this invention incorporates grafted or oligomeric anti-migration agents, whose molecular structures contain segments similar to the resin matrix. During casting and heat setting, these agents can lock themselves and surrounding heat-insulating molecules within the cross-linked network through the dual effects of segment entanglement and chemical anchoring. Combined with the hydrogen bond network formed by the polar hydroxyl groups retained in the PVB resin, this technical feature inhibits the outward migration and precipitation of small molecules within the film under long-term photothermal conditions, maintaining the dimensional stability and long-term weather resistance of the composite film. Attached Figure Description
[0045] Figure 1 This is a flow chart of the preparation process of the heat-insulating PVB composite film of the present invention; Figure 2 This is a schematic diagram of the structural formula of the Cy7-type modified cyanine dye used in this invention; Figure 3 This is a schematic diagram of the structural formula of the fluoroboron pyrrole modified dye used in this invention; Figure 4 This is a schematic diagram of the structure of the polyimide oligomer used in this invention. Detailed Implementation
[0046] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0047] See attached document Figure 1 : Example 1: This embodiment provides a method for preparing a heat-insulating PVB composite film, wherein the components, by weight, include: PVB resin: 60-80 parts, organic conjugated small molecule heat insulation agent: 2-5 parts (organic conjugated small molecule heat insulation agent can be modified cyanine dyes, BODIPY modified dyes, DA structure derivatives, polyimide oligomers or benzobisthiophene conjugated molecules), bio-based plasticizer: 8-15 parts, anti-migration agent: 1-3 parts, antioxidant: 0.2-0.8 parts, UV stabilizer: 0.5-1.5 parts, dispersant: 0.3-0.8 parts. The composite film does not contain any inorganic nanoparticles or inorganic oxide fillers.
[0048] Its preparation method includes the following steps: Pretreatment: Place the PVB resin in an oven at 60-80℃ and dry for 2-4 hours, controlling the moisture content to ≤0.3%, then pulverize it into 50-100 mesh powder; Mix the organic conjugated small molecule heat insulation agent, dispersant, and anti-migration agent, add a small amount of PVB-compatible solvent, and ultrasonically disperse for 15-20 minutes to form a uniform dispersion. In-situ composite: The dried PVB resin powder is added to the reactor, butyraldehyde and solid acid catalyst are added, and the reaction temperature is controlled at 70-80℃ to carry out the acetal reaction for 1.5-2.5h. The above dispersion was then slowly added dropwise, and the reaction continued for 1-1.5 hours. At the same time, bio-based plasticizers, antioxidants, and UV stabilizers were added, and the mixture was stirred at 300-500 r / min until homogeneous. A neutralizing agent was then added to neutralize the catalyst, and a composite resin solution was obtained. Molding: The composite resin solution is cast into a film using a casting machine at a casting temperature of 100-120℃, a casting speed of 0.5-1m / min, and a film thickness of 0.38-1.14mm. Post-processing: Place the formed film in an oven at 100-110℃ for heat setting for 3-5 minutes, cool at 20-30℃, trim the edges, and roll it up to obtain the finished organic conjugated small molecule heat-insulating PVB composite film without inorganic nanofillers.
[0049] Example 2: This embodiment provides a method for preparing a heat-insulating PVB composite film, wherein the components, by weight, include: 65 parts of PVB resin (acetal content 62%, hydroxyl content 22%, viscosity 38 mPa·s, molecular weight 30000), 2.5 parts of benzobisthiophene (BDT) conjugated molecules (with alkoxy modification), 10 parts of furfuryl alcohol plasticizer, 1.5 parts of polyurethane oligomer anti-migration agent, 0.3 parts of antioxidant 1010, 0.8 parts of HALS-grafted PVB anti-UV agent, and 0.3 parts of organic amine dispersant; Its preparation method includes the following steps: The preparation method is basically the same as in Example 1, with only the following adjustments: Ultrasonic dispersion power 350W, time 15min; acetal reaction temperature 70℃, time 1.5h; p-toluenesulfonic acid dosage 0.8% of PVB resin mass. After the reaction was completed, a composite resin solution with a viscosity of 700 mPa·s (25℃) was obtained; The subsequent forming casting temperature is 100℃, the speed is 0.6m / min, and the film thickness is 0.4mm; The heat setting temperature is 100℃ and the time is 3 minutes to obtain the finished composite film.
[0050] Example 3: This embodiment provides a method for preparing a heat-insulating PVB composite film, wherein the components, by weight, include: 75 parts PVB resin (acetal content 68%, hydroxyl content 20%, viscosity 55 mPa·s, molecular weight 40000), 4 parts polyimide oligomer (molecular weight 3000), 14 parts rosin-based plasticizer, 2.5 parts polysiloxane-grafted PVB anti-migration agent, 0.7 parts antioxidant 1010, 1.4 parts HALS-grafted PVB UV stabilizer, and 0.7 parts organic amine dispersant; Its preparation method includes the following steps: The preparation method is basically the same as in Example 1, with only the following adjustments: Ultrasonic dispersion power 450W, time 20min; The acetal reaction was carried out at 80℃ for 2.5 hours, and the amount of p-toluenesulfonic acid used was 1.2% of the mass of the PVB resin. After the reaction was completed, a composite resin solution with a viscosity of 1000 mPa·s (25℃) was obtained; The subsequent forming casting temperature was 120℃, the speed was 0.9m / min, and the film thickness was 0.8mm; The heat setting temperature is 110℃ and the time is 5 minutes to obtain the finished composite film.
[0051] The heat-insulating PVB composite films prepared in Examples 1-3 of this invention can be further applied to high-end automotive glass, high-end architectural glass, photovoltaic glass, high-end display glass, and medical glass. Specifically, the composite film of this invention does not contain any inorganic nanoparticles or inorganic oxide fillers, and the organic components do not shield signals from mobile phones, 5G, automotive radar, etc. Therefore, when the composite film is applied to laminated glass, it can simultaneously possess high light transmittance, low haze, high-efficiency heat insulation, and no signal shielding performance. It can be specifically used in automotive HUD glass laminates, new energy vehicle sunroofs, high-end office building curtain wall glass, photovoltaic module laminated glass, OLED display panel laminated glass, and operating room glass partitions.
[0052] Comparative example: The conventional PVB composite film, by weight, comprises: 70 parts PVB resin (acetal degree 65%, consistent with Example 1, in line with industrial practice), 5 parts ATO nanoparticles (particle size 50nm), 12 parts dibutyl phthalate plasticizer, 0.5 parts dispersant, and 0.5 parts antioxidant 1010. The preparation method adopts a conventional melt blending process (extrusion temperature 155℃) to prepare a composite film with a thickness of 0.5mm (a conventional product of existing technology).
[0053] Test example: For the PVB composite films prepared in Examples 1 to 3 and the comparative examples, their core indicators such as optical properties, thermal insulation, mechanical properties, and weather resistance were quantitatively evaluated according to current national standards. The specific experimental procedures are as follows: According to the GB / T 2410-2008 standard, the visible light transmittance and haze of each group of samples were measured using a transmittance meter at a characteristic wavelength of 550 nm. To eliminate random errors caused by local thickness or surface morphology differences, three samples from different regions were cut for each composite film, and the arithmetic mean of the instrument readings was calculated as the final evaluation criterion.
[0054] The evaluation of thermal insulation performance is based on the GB / T 2680-2021 standard. The sample is fixed flat in the optical path, and the near-infrared band from 780 to 2500 nm is continuously scanned using professional spectrophotometer. The spectral transmission curve is recorded and the near-infrared blocking rate is calculated. Three parallel tests are used to take the average value to ensure the rigor of the data.
[0055] To investigate the long-term residence capacity of organic components in the system, small molecule migration tests were conducted according to GB / T 27707-2011 standard. The samples were placed in a constant temperature environment set at 70℃ and baked continuously for 24 hours. The weight changes before and after the test were accurately compared, and the thermal mobility of the small molecules was calculated accordingly.
[0056] The mechanical strength of the composite film was measured in two dimensions: bulk tensile strength and interfacial adhesion strength. Tensile strength was measured according to GB / T 1040.3-2006 standard, where the film was stretched at a constant tensile rate of 50 mm / min until it broke. Adhesive strength was measured according to GB / T 15763.3-2025 laminated glass standard, where a universal testing machine was used to apply shear load to the laminated glass specimen at room temperature of 25℃ until the interface peeled off.
[0057] In the simulation of extreme outdoor climate, in accordance with the GB / T 16422.2-2014 standard, the samples were exposed to a 750W high-power xenon arc lamp for 100 hours. By comparing the difference in visible light transmittance before and after irradiation, the rate of change in transmittance was obtained, thereby characterizing the material's resistance to ultraviolet aging.
[0058] Finally, to verify the applicability of the material in modern intelligent communication scenarios, in accordance with the GB / T 25471-2010 standard, radio frequency signals in the 2.4GHz and 5GHz bands were emitted to the sample in a test anechoic chamber, and the electromagnetic wave power loss after penetrating the thin film was monitored to determine whether there was a signal shielding phenomenon.
[0059] Test data: Table 1. Comparison of overall performance test results between the examples and comparative examples The "—" indicates that no test was conducted.
[0060] Conclusion: Based on the above performance test results, a detailed analysis was conducted on the performance differences and technical advantages of Examples 1-3 of the present invention and the comparative example (traditional inorganic nanofiller type PVB), verifying the effectiveness and superiority of the technical solution of the present invention based on 60%-70% acetal degree PVB resin. Examples 1-3 exhibited visible light transmittance of 88.4%-89.0% and haze of 0.30%-0.39%, both meeting the performance indicators set by this invention (transmittance ≥88%, haze ≤0.5%). In contrast, the comparative examples showed visible light transmittance of only 83.5% and haze as high as 1.46%, a significant difference. The core reason lies in: The example uses organic conjugated small molecules as the heat insulation medium, which are molecularly dispersed in a 60%-70% acetal PVB matrix. There is no light scattering caused by particle agglomeration, which ensures high light transmittance and low haze from the source. Meanwhile, 60%-70% acetal-rich PVB resin itself has good optical properties and excellent compatibility with organic conjugated small molecules, further enhancing optical stability; while the comparative ratio uses ATO nanoparticles, particle aggregation is difficult to completely avoid, resulting in severe light scattering, leading to decreased light transmittance and increased haze, which cannot meet the optical performance requirements of high-end scenarios.
[0061] The near-infrared blocking rates of Examples 1-3 were 90.7%-94.1%, all ≥90%. Example 3, using polyimide oligomers (with a wide near-infrared absorption band) and having a thicker film, achieved the highest blocking rate (94.1%), slightly higher than the comparative example (89.6%). This indicates that the thermal insulation efficiency of organic conjugated small molecules is no lower than that of traditional inorganic nanofillers, and that molecular design can further enhance the thermal insulation performance. Simultaneously, the 60%-70% acetal-grade PVB resin has a high hydroxyl content, which can form stronger hydrogen bonds with the organic conjugated small molecules. Combined with the anchoring effect of the anti-migration agent, this effectively inhibits the migration of small molecules.
[0062] Regarding the small molecule migration rate, the migration rates of Examples 1-3 were 0.19%-0.26%, all ≤0.3%, indicating that through in-situ composite process and the action of anti-migration agent, organic conjugated small molecules can be stably bound to 60%-70% acetal degree PVB molecular chains without obvious migration or precipitation. In contrast, the use of inorganic nanoparticles eliminates the problem of small molecule migration, but it poses a risk of long-term thermal insulation performance degradation due to particle aggregation and sedimentation (this was not reflected in the test, but will become apparent after long-term use).
[0063] The tensile strength of Examples 1-3 was 21.0-23.4 MPa, and the bond strength was 8.3-9.2 MPa, both superior to the comparative examples (tensile strength 18.6 MPa, bond strength 7.6 MPa), and both met the set performance indicators. The reason is: Organic conjugated small molecules are tightly bound to 60%-70% acetal PVB through hydrogen bonds and π-π interactions, which enhances the interfacial bonding of the blend system. Meanwhile, the bio-based plasticizer has excellent compatibility with 60%-70% acetal degree PVB, which can effectively compensate for the possible decrease in flexibility caused by the reduction in acetal degree and improve the flexibility and mechanical properties of the membrane. In contrast, the agglomeration of ATO nanoparticles in the comparison ratio leads to stress concentration, resulting in a decrease in the mechanical properties of the membrane.
[0064] After 100 hours of xenon arc lamp irradiation, the transmittance change rate in Examples 1-3 was only 1.3%-1.9%, far lower than that in the comparative example (3.3%), indicating that the composite film of the present invention has excellent aging resistance. The core reason is: The selected organic conjugated small molecules (modified cyanine, BDT, polyimide oligomers) have good aging resistance and, when combined with HALS-grafted PVB UV stabilizers, form a synergistic anti-aging system that can effectively protect the small molecules and PVB molecular chains from UV damage. Meanwhile, the molecular structure of 60%-70% acetal PVB resin is stable. After being protected by antioxidants, it can inhibit aging degradation and further improve aging resistance. In contrast, the ATO nanoparticles in the comparative example are prone to photocatalytic degradation under ultraviolet irradiation, resulting in a significant decrease in the light transmittance of the film and poor aging resistance.
[0065] Examples 1-3 all showed no signal shielding (no significant signal attenuation in the 2.4GHz and 5GHz bands), while the comparative examples showed significant signal shielding (signal attenuation ≥15dB). This is one of the core advantages of this invention. The reason is: The embodiment completely eliminates inorganic metal oxide fillers, and the organic components do not have a shielding effect on electromagnetic waves, making it perfectly suitable for scenarios with high signal compatibility requirements such as vehicle HUDs and smart buildings. In contrast, the ATO nanoparticles in the comparative example are metal oxides, which shield electromagnetic waves and limit their application in high-end intelligent scenarios.
[0066] Examples 1-3 use 60%-70% acetal degree PVB resin. After the preparation process is optimized, the reaction temperature is reduced and the processing energy consumption is reduced. No special equipment is required, and it can be directly adapted to existing PVB production lines. The processing convenience is better than that of high acetal degree PVB formulations. Meanwhile, the raw materials used are all of commonly used industrial specifications, which are easy to procure and cost-controllable, enabling large-scale mass production. Although the comparative ratio uses PVB resin with the same acetal degree, it requires additional grinding and dispersion pretreatment due to the addition of inorganic nanofillers, making the process complex and causing severe equipment wear.
[0067] Figure 2 This is a representative structural formula of a modified cyanine dye used in this invention. The dye belongs to the heptamethine cyanine (Cy7) series, and its core structure consists of two indoline units linked by a polymethyl chain containing seven methines (-CH=). This conjugated system endows the dye with strong absorption characteristics in the near-infrared region (NIR-I window), with its maximum absorption wavelength typically located at 740-750 nm and its emission wavelength at 770-780 nm.
[0068] To meet the application requirements of PVB composite films, this invention modifies Cy7 dye by introducing hydrophobic alkyl groups (such as long-chain alkyl C9 groups) or rigid structures. Taking Cy7-C9 as an example, its molecular structure mainly consists of three parts: a central multi-conjugated benzene ring system, amine substituents at both ends, and a hydrophobic carbon chain. The introduction of hydrophobic groups has the following functions: Enhance the compatibility between dyes and PVB resins to avoid phase separation due to polarity differences; Reduce the migration tendency of dyes under humid and hot conditions and improve the long-term stability of composite films; The introduction of rigid structures can improve the photostability of dye molecules and suppress photobleaching. Figure 2 The structure shown is the general formula structure of Cy7-type cyanine dyes with the above-mentioned hydrophobic modification characteristics.
[0069] Figure 3 This is a representative structural formula of a fluoroboron pyrrole (BODIPY, i.e., boron fluoride complexed dipyrrolemethyl methacrylate) modified dye used in this invention. The core structure of the BODIPY dye is a rigid conjugated framework formed by boron atoms complexed with two pyrrole rings. This parent structure has excellent optical properties, including a high molar extinction coefficient, good photostability, and chemical stability.
[0070] To achieve absorption in the near-infrared region, this invention modifies the BODIPY matrix using conjugated extension. Specific modification strategies include: Substituents such as pyrrole and aryl are introduced at the 3 and 5 positions of the parent structure to increase the range of conjugated systems. Introducing electron-donating groups such as triphenylamine and thiophene at the meso position (8 position) causes a red shift in the absorption spectrum; By connecting two BODIPY units with bridging groups such as benzothiadiazole or benzodithiophene, the conjugation length is further extended. After the above modification, the maximum absorption wavelength of this type of dye can be extended to 728 nm and above, accurately covering the near-infrared region and meeting the requirements of thermal insulation applications for absorption in the 780-2500 nm band.
[0071] Figure 3 The structure shown is the general formula of the modified BODIPY dyes described above. Its molecular design ensures good dispersibility and near-infrared absorption efficiency in the PVB matrix.
[0072] Figure 4 This is a representative structural formula of a polyimide oligomer used in this invention. Polyimide oligomers are low-molecular-weight oligomers formed by the condensation reaction of dianhydride monomers and diamine monomers, with molecular weight controlled in the range of 1000-5000. Their molecular chains contain a characteristic imide ring structure (-CO-N-CO-), which endows the material with excellent high-temperature resistance and chemical stability.
[0073] When used as a thermal insulation agent, the near-infrared absorption mechanism of polyimide oligomers mainly originates from the intrinsic absorption of near-infrared light by the conjugated structure of the molecular chain, as well as the overtone absorption in the 1000-1700 nm wavelength range generated by the stretching and deformation vibrations of the CH bonds. Controlling the molecular weight to a low-molecular-weight state of 1000-5000 ensures good compatibility with PVB resin while avoiding the processing difficulties and excessively high melting temperatures associated with high-molecular-weight polyimides. Simultaneously, the end functional groups retained on the oligomeric chains, such as anhydride and amino groups, can form hydrogen bonds with the hydroxyl groups on the PVB molecular chain, enhancing interfacial bonding and further improving the mechanical properties and thermal insulation stability of the composite film.
[0074] Figure 4 The structure shown is a representative general formula of the above-mentioned polyimide oligomers, reflecting the structural characteristics of the imide ring backbone and appropriate molecular chain length.
Claims
1. A heat-insulating PVB composite film, characterized in that, The composite membrane does not contain any inorganic nanoparticles or inorganic oxide fillers, and is made from raw materials comprising the following parts by weight: PVB resin: 60-80 parts; Organic conjugated small molecule heat insulation agent: 2-5 parts; Bio-based plasticizer: 8-15 parts; Anti-migration agent: 1-3 parts; Antioxidant: 0.2-0.8 parts; UV stabilizer: 0.5-1.5 parts; Dispersant: 0.3-0.8 parts.
2. The heat-insulating PVB composite film according to claim 1, characterized in that, The composite membrane is made from raw materials comprising the following parts by weight: PVB resin: 65-75 parts; Organic conjugated small molecule heat insulation agent: 2.5-4 parts; Bio-based plasticizer: 10-14 parts; Anti-migration agent: 1.5-2.5 parts; Antioxidant: 0.3-0.7 parts; UV stabilizer: 0.8-1.4 parts; Dispersant: 0.3-0.7 parts.
3. The heat-insulating PVB composite film according to claim 1, characterized in that, The organic conjugated small molecule heat insulation agent is a modified cyanine dye, a BODIPY-type modified dye, a DA structure derivative, a polyimide oligomer, or a benzobisthiophene-type conjugated molecule; The bio-based plasticizer is a furfuryl alcohol-based plasticizer or a rosin-based plasticizer.
4. The heat-insulating PVB composite film according to claim 1, characterized in that, The anti-migration agent is a polyurethane oligomer anti-migration agent or a polysiloxane-grafted PVB anti-migration agent. The UV-resistant agent is a HALS-grafted PVB UV-resistant agent; The dispersant is an organic amine dispersant; The antioxidant is antioxidant 1010.
5. The heat-insulating PVB composite film according to claim 1, characterized in that, The PVB resin has an acetal degree of 62%-68%, a hydroxyl content of 20%-22%, a viscosity of 38-55 mPa·s, and a molecular weight of 30,000-40,000.
6. A method for preparing a heat-insulating PVB composite film as described in any one of claims 1-5, characterized in that, Includes the following steps: PVB resin is dried and pulverized to obtain PVB resin powder; Organic conjugated small molecule heat insulation agent, dispersant and anti-migration agent are mixed, PVB-compatible solvent is added, and ultrasonic dispersion is formed to form a uniform dispersion. The dried PVB resin powder was added to the reaction vessel, and butyraldehyde and solid acid catalyst were added to carry out the acetal reaction. The uniformly dispersed liquid was then slowly added dropwise to continue the reaction. At the same time, a bio-based plasticizer, antioxidant, and UV stabilizer were added and stirred until homogeneous. A neutralizer was then added to neutralize the catalyst, resulting in a composite resin solution. The composite resin solution is cast into a film using a casting machine; The formed film is heat-set, cooled, trimmed, and wound up to obtain the finished organic conjugated small molecule heat-insulating PVB composite film without inorganic nanofillers.
7. The preparation method according to claim 6, characterized in that, In the step of drying and pulverizing PVB resin, the PVB resin is placed in an oven at 60-80℃ and dried for 2-4 hours, with the moisture content controlled to be ≤0.3%, and then pulverized into powder of 50-100 mesh. In the step of forming a uniform dispersion, the ultrasonic dispersion power is 350-450W and the ultrasonic dispersion time is 15-20min.
8. The preparation method according to claim 6, characterized in that, In the acetal reaction step, the reaction temperature is controlled at 70-80℃, the reaction time is 1.5-2.5h, the solid acid catalyst is p-toluenesulfonic acid, and the amount of p-toluenesulfonic acid used is 0.8%-1.2% of the mass of PVB resin; The reaction time after adding the uniformly dispersed liquid is 1-1.5 hours. At the same time, bio-based plasticizers, antioxidants, and UV stabilizers are added and stirred at 300-500 r / min until homogeneous. The viscosity of the composite resin solution obtained after the reaction was controlled at 700-1000 mPa·s at 25℃.
9. The preparation method according to claim 6, characterized in that, In the film casting step, the casting temperature is 100-120℃, the casting speed is 0.5-1m / min, and the film thickness is controlled at 0.38-1.14mm; In the heat setting step, the heat setting temperature is 100-110℃, the heat setting time is 3-5 minutes, and then cooling is performed at 20-30℃.
10. An application of the heat-insulating PVB composite film as described in any one of claims 1-5, characterized in that, The composite film is used in high-end automotive glass, high-end architectural glass, photovoltaic glass, high-end display glass, and medical glass. The composite film, as a sandwich layer with high light transmittance, low haze, high-efficiency heat insulation and no signal shielding performance, is used in automotive HUD glass sandwich layers, new energy vehicle skylight glass, high-end office building curtain wall glass, photovoltaic module sandwich glass, OLED display panel sandwich glass, and operating room glass partitions.